PENGEMBANGAN BUSINESS MODEL INNOVATION (BMI) PADA UKM DI KABUPATEN KOLAKA DENGAN PENDEKATAN KONFIGURASI - Sudarnice Sudarnice; La Sudarman (Program Sarjana Manajemen Universitas Internasional Batam, 2022)
The topic raised in this research is the emphasis on the relevance of Business Model Innovation (BMI). Based on this, the purpose of this study is to explore the management approach and Business Model Innovation (BMI) to foster SMEs in Kolaka Regency with an approach that connects management capabilities to Business Model Innovation (BMI). This is purposively from 89 SMEs in Kolaka Regency, Southeast Sulawesi Province by adopting the Qualitative Comparative Analysis (QCA) method. The data analysis technique used in this study also uses the concept of Structural Equatin Modeling (SEM) with the Partial Least Square (PLS) program using a configuration approach, the results show that management ability shows a significant influence on Business Model Innovation (BMI). The results of fsQCA strengthen these findings and refine SEM which provides good conditions for the development of Business Model Innovation (BMI).